Macrophage colony‐stimulating factor pretreatment of bone marrow progenitor cells regulates osteoclast differentiation based upon the stage of myeloid development. Issue 8 (25th February 2019) - Yang, Xuehui; Pande, Shivangi; Scott, Cameron; Friesel, Robert
Abstract: Osteoclasts (OCs) are large, multinucleated bone resorbing cells originating from the bone marrow myeloid lineage, and share a common progenitor with macrophages and dendritic cells. Bone marrow cells (BMCs) are a common source for in vitro osteoclastogenesis assays but are a highly heterogeneous mixture of cells. Protocols for in vitro osteoclastogenesis vary considerably thus hindering interpretation and comparison of results between studies. Macrophage colony‐stimulating factor (M‐CSF) pretreatment is commonly used to expand OC progenitors (OCPs) in BMC cultures before in vitro differentiation. However, the failure of osteoclastogenesis of M‐CSF primed bone marrow myeloid blasts has been reported. In this study, we used a simple method of differential adherence to plastic to enrich OCP from mouse BMCs. We found that M‐CSF pretreatment of plastic‐adherent BMCs (adBMCs) increased the number of CD11b‐F4/80+ macrophages and decreased the number of CD11b+ monocytes resulting in decreased OC formation. M‐CSF pretreatment of purified c‐Kit+ progenitors weakly inhibited OC formation, whereas M‐CSF pretreatment of purified c‐Kit‐CD11b+ progenitors promoted the formation of large OC. M‐CSF pretreatment increased the proliferation of both purified c‐Kit+ and c‐Kit‐CD11b+ cells and increased the percentage of CD11b‐F4/80+ cells from c‐Kit+ progenitors. In addition, M‐CSF pretreatment increased the percentage of CD11b+ F4/80− cells from purified c‐Kit‐CD11b+ cells. M‐CSF pretreatment increased the percentage of CD14 + CD16 + intermediate monocytes and subsequent OC formation from human 2adBMCs, and increased OC formation of purified CD14 + cells. Together, these results indicate that in vitro OCP expansion in the presence of M‐CSF and bone marrow stromal cells is dependent upon the developmental stage of myeloid cells, in which M‐CSF favors macrophage differentiation of multipotent progenitors, promotes monocyte maturation and supports differentiation of late‐stage OCP cells. Abstract : Macrophage colony‐stimulating factor (M‐CSF) has been widely used in osteoclast differentiation assays with varying results. Here we show that M‐CSF pretreatment of bone marrow cells promotes macrophage differentiation while reducing expansion and differentiation of osteoclast progenitor cells. These results indicated that use of M‐CSF for osteoclast differentiation assays should be used and interpreted with caution.